2022
DOI: 10.1177/21582440211068485
|View full text |Cite
|
Sign up to set email alerts
|

Economic Uncertainty and Exchange Market Pressure: Evidence From China

Abstract: This paper evaluates the impact of local and external economic uncertainty shocks on China’s exchange market pressure from a time-varying perspective. We first construct a simple behavioral model to provide some economic background for our empirical analysis. The model identifies two channels, namely market sentiment and market demand, through which economic uncertainty has a time-varying impact on exchange market pressure. Notably, we calculate a new exchange market pressure index for China by considering Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…In country-specific studies, related findings also show that ERV in developing economies is not only influenced by their own EPU but is also subject to the significant influence of EPU in developed economies. For example, for the ERV of the Chinese RMB, studies have shown that it is significantly influenced not only by Chinese EPU but also by US, European and Japanese EPU [ 12 , 18 20 ]; for the ERV of the Mexican peso, it is also influenced by both domestic EPU and foreign EPU [ 21 ]. Regarding the ERV of currencies of developed economies, related studies have found that they are mainly influenced by EPU within developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…In country-specific studies, related findings also show that ERV in developing economies is not only influenced by their own EPU but is also subject to the significant influence of EPU in developed economies. For example, for the ERV of the Chinese RMB, studies have shown that it is significantly influenced not only by Chinese EPU but also by US, European and Japanese EPU [ 12 , 18 20 ]; for the ERV of the Mexican peso, it is also influenced by both domestic EPU and foreign EPU [ 21 ]. Regarding the ERV of currencies of developed economies, related studies have found that they are mainly influenced by EPU within developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…The estimation procedures are robust to cross-sectional dependency and slope heterogeneity. Liu (2022) employed time-varying parameter vector autoregression to investigate the impact of economic policy uncertainty on EMP in China.…”
Section: Introductionmentioning
confidence: 99%